A phase I study of high dose camostat mesylate in healthy adults provides a rationale to repurpose the TMPRSS2 inhibitor for the treatment of COVID‐19 - Junsaku Kitagawa; Hayato Arai; Hiroyuki Iida; Jiro Mukai; Kenji Furukawa; Seitaro Ohtsu; Susumu Nakade; Tomohiro Hikima; Miwa Haranaka; Naoto Uemura (Wiley, 2021)
Abstract Camostat mesylate, an oral serine protease inhibitor, is used to treat chronic pancreatitis and reflux esophagitis. Recently, camostat mesylate and its active metabolite 4‐(4‐guanidinobenzoyloxy)phenylacetic acid (GBPA) were reported to inhibit the infection of cells by severe acute respiratory syndrome coronavirus 2 by inhibiting type II transmembrane serine protease. We conducted a phase I study to investigate high‐dose camostat mesylate as a treatment for coronavirus disease 2019. Camostat mesylate was orally administered to healthy adults at 600 mg 4 times daily under either of the following conditions: fasted state, after a meal, 30 min before a meal, or 1 h before a meal, and the pharmacokinetics and safety profiles were evaluated. In addition, the time of plasma GBPA concentration exceeding the effective concentration was estimated as the time above half‐maximal effective concentration (EC50) by using pharmacokinetic/pharmacodynamic modeling and simulation. Camostat mesylate was safe and tolerated at all dosages. Compared with the fasted state, the exposure of GBPA after a meal and 30 min before a meal was significantly lower; however, no significant difference was observed at 1 h before a meal. The time above EC50 was 11.5 h when camostat mesylate 600 mg was administered 4 times daily in the fasted state or 1 h before a meal. Based on the results of this phase I study, we are currently conducting a phase III study.